Japan’s Strategy in Internationalization of Small and Medium Sized Firms: A Case Study of Japan Internship Program - Firman Budianto (Global Strategis, 2020)
The changing labor market following the economic and socio-cultural changes in Japan, on the one hand, drives the country to increase the entry of foreign workforces, including highly skilled foreign professionals. On the other hand, number of studies on global talents in Japanese workplace demonstrates a call for structural reforms in the Japanese firms as highly skilled global talents, from their own perspective, are struggling to integrate into Japanese firms due to multiple factors. By using qualitative data from document and content analysis, this present study contributes to the growing discourse on global talents mobility in the changing Japanese corporations by discussing, from Japan side, their strategies in dealing with the emerging needs of foreign workforces. Based on a case study of METI Japan Internship Program, this study finds that Japanese government in collaboration with Japanese firms start to promote an internship program for international young talents and make use of their cultural capital to not only support host companies’ business expansion, but also to expand crosscultural exposure in the workplace and challenge the existing HRM practice of the companies. Being facilitated by the Japanese government, the program is beneficial for Japanese firms and may serve as a stepping stone for the students to work in Japanese firms in the future. This present study, therefore, suggests that global internship paves a way in channeling global talents to Japan and plays an increasingly crucial role in promoting emerging forms of internationalization within Japanese corporations.Keywords: Global talent, Internationalization of Japanese firms, Japan Internship Program, Skilled migrationPasar tenaga kerja yang berubah mengikuti perubahan ekonomi dan sosial-budaya di Jepang, di satu sisi, mendorong Jepang untuk memfasilitasi masuknya tenaga kerja asing, terutama, profesional asing terampil. Di sisi lain, sejumlah studi tentang talenta global di Jepang menunjukkan adanya urgensi reformasi struktural di perusahaan-perusahaan Jepang karena pekerja asing terampil tersebut menghadapi berbagai tantangan untuk berintegrasi ke perusahaan-perusahaan Jepang. Dengan menggunakan data kualitatif dari analisis dokumen, penelitian ini berkontribusi terhadap diskursus mobilitas talenta global dalam perusahaan Jepang dengan membahas, dari sudut pandang Jepang, strategi mereka dalam menghadapi peningkatan kebutuhan tenaga kerja asing terampil. Berdasarkan studi kasus Program Magang Jepang METI, studi ini menemukan bahwa pemerintah Jepang bekerja sama dengan perusahaan-perusahaan Jepang telah memulai program magang untuk talenta muda internasional dan memanfaatkan keterampilan mereka untuk tidak hanya mendukung ekspansi bisnis perusahaan Jepang, tetapi juga untuk mempromosikan komunikasi lintas budaya di tempat kerja dan mengritik praktik manajemen SDM perusahaan yang berjalan. Dengan dukungan Pemerintah Jepang, program ini bermanfaat bagi perusahaan Jepang dan dapat berfungsi sebagai batu loncatan bagi para peserta untuk bekerja di perusahaan Jepang di masa depan. Penelitian ini, oleh karena itu, menunjukkan bahwa program magang global membuka jalan bagi para latenta global untuk berkarier di Jepang dan semakin memainkan peran dalam mempromosikan internasionalisasi dalam perusahaan Jepang.Kata-kata kunci: Internasionalisasi Perusahaan Jepang, Japan Internship Program, Migrasi terampil, Talenta Global